Answer:
y = (-4/3)*x + 7
Explanation:
The point-slope form of the equation of a line is: y = a*x + b
In the above equation, a is the slope of the line representing the equation in the graph and y is the function of x [y = y(x)]
The given line has a slope of -4/3, so that a = -4/3
=> The equation of this line has a form as following: y = (-4/3)*x + b (1)
As the line passes through the point (9; -5) (in which: x = 9; y = -5). Replace x =9 and y = -5 into the equation (1), we have:
y = (-4/3)*x + b
=> -5 = (-4/3)*9 + b
=> -5 = -12 + b
=> b = 7
So that the equation in point-slope form of the given line is:
y = (-4/3)*x + 7